Development of an educational tool on tinnitus in a website format - Carvalho,Raissa Pereira (2020)
ABSTRACT Objective: to develop an educational tool in a Virtual Learning Environment (VLE), in a website format, to supply information on tinnitus, additional content on hearing and to provide access links to other websites related to speech therapy and audiology, so as to promote public health. Methods: an experimental, descriptive study, involving, in its construction, 6 stages elaborated as follows: planning, adaptation, collection of testimonies, inclusion of content, review and dissemination. Results: the site was titled "Do you have tinnitus?" It was subdivided into others: "Home", "Tinnitus?" "Types of tinnitus," "Main causes," "What to do?" "Main forms of treatment," "Tips to relieve tinnitus," "Prevention," "News," "Testimonials," "About your hearing," "What is hearing loss?" "What are speech therapy and audiology?" "Other sites," "Contact" and "About." Illustrations and videos were inserted, and the information contained in any material was classified with easy readability. Conclusion: it was possible to develop a website entitled “Do you have tinnitus?” available at the electronic address: https://vocetemzumbido.wixsite.com/home, providing general information about tinnitus, in addition to additional information on hearing.